2021
DOI: 10.2298/tsci200721241s
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of CNG powered vehicles in the transition to zero emission mobility - example of the light commercial vehicles fleet

Abstract: The aim of paper was to discuss contribution of bi-fuel CNG powered light commercial vehicles to the Well-To-Wheel CO2 equivalent emissions, both today and in the coming decades in which the development of new fuels and new vehicles is expected. Field research was done in Belgrade, during one year, using Euro 5 diesel/LPG/CNG light commercial vehicles driving under low vehicle speed, low engine load, low exhaust gas temperature and high number of stops. WTW as neutral methodology was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Subsequent analysis of CO2 emissions over the TTW cycle showed that it is most favorable for gasoline/CNG fueled engines, which consume 28.8% and 6.7% less CO2 than gasoline/LPG and diesel vehicles, respectively [19]. Comparing this to the other multifuel configurations, the diesel/CNG CO2 emissions are 13.5% lower than the gasoline/LPG and even 1.5% lower than the diesel vehicles considered in this study.…”
Section: Introductionmentioning
confidence: 63%
“…Subsequent analysis of CO2 emissions over the TTW cycle showed that it is most favorable for gasoline/CNG fueled engines, which consume 28.8% and 6.7% less CO2 than gasoline/LPG and diesel vehicles, respectively [19]. Comparing this to the other multifuel configurations, the diesel/CNG CO2 emissions are 13.5% lower than the gasoline/LPG and even 1.5% lower than the diesel vehicles considered in this study.…”
Section: Introductionmentioning
confidence: 63%